Economic Condition of the Tharu: A Study of Kalika Municipality of Chitwan District - Dhakal, Chadra Prasad (Interdisciplinary Journal of Management and Social Sciences, 2021)
The study analyzes the socio-economic status of the Tharu living in Kalika municipality of Chitwan. Kalika municipality ward number 4 is the traditional home land of Tharus. This ward is the Padampur VDC which was shifted from the area of Chitwan national park (Chiriya) to current place in 2057. The study is only limited on ward number 4 of Kalika municipality and focuses on current economic situation and the factors that play important role in to form economic status of the Tharu of Study area. The study follows the both qualitative and quantitative research design and both primary and secondary source of data were used in this study. Conclusion of this study has based on data analysis and presentation.